Investigation on the antimicrobial properties of cerium‐doped bioactive glasses. Issue 2 (4th August 2021) - Raimondi, Stefano; Zambon, Alfonso; Ranieri, Raffaella; Fraulini, Francesca; Amaretti, Alberto; Rossi, Maddalena; Lusvardi, Gigliola
Abstract: Cerium‐doped bioactive glasses (Ce‐BGs) are implant materials that present high biocompatibility, modulate the levels of reactive oxygen species, and exert antimicrobial activity. The potential of BGs, 45S5, and K50S derived glasses doped with CeO2 (1.2, 3.6, and 5.3 mol%) to inhibit the growth of pathogen microbes was thoroughly investigated according to the ISO 22196:2011 method properly adapted. A significant reduction of the E. coli charge was detected in all glasses, including the BGs without cerium. The evolution of pH of the medium not inoculated following the immersion of the Ce‐BGs was monitored. The presence of cerium did not affect markedly the pH trend, which increased rapidly for both compositions. The change of pH was strongly mitigated by the presence of 200 mM phosphate buffer pH 7.0 (PB) in the medium. In media buffered by PB, the growth of E. coli, Pseudomonas aeruginosa, Listeria monocytogenes, Staphylococcus aureus, and C. albicans was not affected by the presence of BGs doped or not with cerium, suggesting that the antibacterial activity of Ce‐BGs is linked to the increase of environmental pH rather than to specific ion effects. However, Ce‐BGs resulted promising biomaterials that associate low toxicity to normal cells to a considerable antimicrobial effect, albeit the latter is not directly associated with the presence of cerium.